Influence of Pilates Method on Nonspecific Lumbar Pain - Schimidt, Ana Carla; Herzinger, Paula de Oliveira; Matias, Danielle Pacheco; Welling, Leonardo C. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Low back pain is defined as pain located between the lower rib cage and the gluteal folds, and its etiology is multifactorial, considerably affecting quality of life. The aim of this literature review was to analyze the influence of the Pilates method on the symptoms of patients with nonspecific low back pain, which is considered a promising treatment for this type of pathology. A narrative review of the literature was carried out using the PubMed, Pedro, Scopus and Scielo databases. To perform the search, Pilates AND Low back nonspecific AND Pain were used as keywords. Articles published in the last 5 years, randomized clinical trials that verified the influence of the Pilates method in adult individuals with unspecified low back pain and full text in English were included. Of the 77 articles identified, 7 articles met the inclusion criteria, 7 analyzed the primary outcomes of pain intensity and disability, 5 articles compared Pilates with other rehabilitation techniques and 2 studies compared the effectiveness of Pilates solo with Pilates apparatus. It was concluded that all the techniques that were compared with Pilates are effective, being difficult to affirm the superiority of Pilates over them in relation to the reduction of pain and disability and improvement of quality of life. However, the Pilates method has shown good results in pain perception and intensity, functional capacity, fear of movement and the idea that movement can worsen your condition, muscle strength, range of motion and flexibility.
Keywords: pilates; low back pain; physiotherapy